Contribution of Maqashid Syari'ah to Sustainable Economic Development: A Conceptual Review - Muh. Fauzi Isnan; Supriadi Supriadi; Kamaruddin Kamaruddin (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
This article aims to analyze the contribution of Maqasid al-Shariah to sustainable economic development from the perspective of contemporary Islamic economics. Maqasid al-Shariah, which encompasses the protection of religion, life, intellect, lineage, and property, serves as a fundamental normative framework in designing an economic system that is not only materially just but also fulfills the spiritual and social needs of society. Using a qualitative approach based on library research, this article examines classical and contemporary literature to explain how the principles of Maqasid al-Shariah are implemented in Islamic financial sectors, wealth distribution, halal financial product innovation, and economic policies grounded in social justice. The analysis reveals that the application of Maqasid al-Shariah can provide strategic direction in establishing an inclusive, just, and sustainable Islamic economic system. This article also highlights implementation challenges, including the need for Shariah-compliant regulations that are adaptable to technological advancements and the complexities of global markets. Therefore, Maqasid al-Shariah is not only theoretically relevant but also carries significant practical implications for promoting public welfare and prosperity within the context of the modern economy.